The protective immunity induced by intranasally inoculated serotype 63 chimpanzee adenovirus vector expressing human respiratory syncytial virus prefusion fusion glycoprotein in BALB/c mice - Huang, Lei; Liu, Mei-Qing; Wan, Chang-Qing; Cheng, Ning-Ning; Su, Yan-Bin; Zheng, Yan-Peng; Peng, Xiang-Lei; Yu, Jie-Mei; Fu, Yuan-Hui; He, Jin-Sheng (Frontiers in Microbiology, 2022)
Human respiratory syncytial virus (RSV) is a ubiquitous pediatric pathogen causing serious lower respiratory tract disease worldwide. No licensed vaccine is currently available. The serotype 26 human adenovirus vector encoding pre-fusion conformation stabilized RSV-F protein (Ad26.RSV.preF) has proceeded to phase III clinical trial. In this work, our goal is to construct the serotype 63 chimpanzee adenovirus vector expressing pre-fusion conformation stabilized RSV-F protein (rChAd63/mDS-Cav1) and investigate the immune efficacy and safety in vivo. After immunizing mice via intranasal route, the rChAd63/mDS-Cav1 induced enhanced neutralizing antibody and specific CD8+ T cell responses as well as good immune protection with the absence of enhanced RSV disease (ERD) in BALB/c mice. The results indicate that rChAd63-mDS-Cav1 is a promising mucosal vaccine candidate against RSV infection and may represent effective and safe vaccine vector.